2023
DOI: 10.3390/molecules28155669
|View full text |Cite
|
Sign up to set email alerts
|

Fascinating Furanosteroids and Their Pharmacological Profile

Abstract: This review article delves into the realm of furanosteroids and related isoprenoid lipids derived from diverse terrestrial and marine sources, exploring their wide array of biological activities and potential pharmacological applications. Fungi, fungal endophytes, plants, and various marine organisms, including sponges, corals, molluscs, and other invertebrates, have proven to be abundant reservoirs of these compounds. The biological activities exhibited by furanosteroids and related lipids encompass anticance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 223 publications
0
29
0
Order By: Relevance
“…Based on these de facto principles, four groups of steroids or triterpenoids can be distinguished [1][2][3][4][5]7,14,15]. The first group includes steroids in which the A ring is reduced by one carbon atom.…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…Based on these de facto principles, four groups of steroids or triterpenoids can be distinguished [1][2][3][4][5]7,14,15]. The first group includes steroids in which the A ring is reduced by one carbon atom.…”
Section: Figurementioning
confidence: 99%
“…The fourth group includes steroids in which the D ring is reduced by one or two carbon atoms, and these are D-norsteroids [16,17]. The most interesting for this review is the information about A, B, C, and D-norsteroids, which are found in marine organisms and algae and are also synthesized by fungi or fungal endophytes [1][2][3][4][5][6][7][8]16,17].…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations